Evaluation of [68Ga]Ga-NODAGA-RGD for PET Imaging of Rat Autoimmune Myocarditis - Jahandideh Aghavan; Ståhle Mia; Virta Jenni; Li Xiang-Guo; Liljenbäck Heidi; Moisio Olli; Knuuti Juhani; Roivainen Anne; Saraste Antti (Front Med, 2022)
The 68Gallium-labeled 1,4,7-triazacyclononane-1-glutaric acid-4,7-diacetic acid conjugated radiolabelled arginine-glycine-aspartic acid peptide ([68Ga]Ga-NODAGA-RGD) is a positron emission tomography (PET) tracer binding to cell surface receptor αvβ3 integrin that is upregulated during angiogenesis and inflammation. We studied whether αvβ3 targeting PET imaging can detect myocardial inflammation in a rat model of autoimmune myocarditis. To induce myocarditis, rats (n = 8) were immunized with porcine cardiac myosin in complete Freund's adjuvant on days 0 and 7. Control rats (n = 8) received Freund's adjuvant alone. On day 21, in vivo PET/CT imaging with [68Ga]Ga-NODAGA-RGD followed by ex vivo autoradiography and immunohistochemistry were carried out. Inflammatory lesions were detected histologically in the myocardium of 7 out of 8 immunized rats. In vivo PET images showed higher [68Ga]Ga-NODAGA-RGD accumulation in the myocardium of rats with inflammation than the non-inflamed myocardium of control rats (SUVmean 0.4 ± 0.1 vs. 0.1 ± 0.02; P = 0.00006). Ex vivo autoradiography and histology confirmed that [68Ga]Ga-NODAGA-RGD uptake co-localized with inflammatory lesions containing αvβ3 integrin-positive capillary-like structures. A non-specific [68Ga]Ga-DOTA-(RGE)2 tracer showed 76% lower uptake than [68Ga]Ga-NODAGA-RGD in the inflamed myocardium. Our results indicate that αvβ3 integrin-targeting [68Ga]Ga-NODAGA-RGD is a potential PET tracer for the specific detection of active inflammatory lesions in autoimmune myocarditis.